ASSESSMENT OF THE IMPACT OF COORPERATIVE SOCIETIES ON WOMEN EMPOWERMENT IN GOMBE METROPOLIS, GOMBE STATE NIGERIA - SATI, REBECCA; KIM, IDOMA; COMFORT, NNAJI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This study assessed the impact of cooperative societies on women empowerment in Gombe metropolis, Gombe Sate Nigeria. The study examined the socio-economic characteristics of women cooperatives in Gombe metropolis, identifies the sources of income of the cooperative societies, assessed the impact of cooperative societies on women empowerment and investigated the challenges faced by the cooperative societies. Data was gathered from systematically selected women based on Taro Yamene formula with error margin of 0.01 (10%) out of the 19 registered and functional cooperatives in Gombe metropolis. Descriptive statistics were employed in analyzing the data which found that the predominant sources of income of the cooperative societies was membership contributions (30%), 53% of the respondents said that they benefitted from the dividends shared by the cooperatives, which some used in acquiring landed properties and payment of children’s school fees (30% and 27%) respectively. Relationship between the socio-economic characteristics of the cooperators as independent variables and participation in cooperatives as dependent variable was tested using chi-square, the result shows that out of seven independent variables, six were statistically significant. The study concluded that women cooperators have been moderately empowered economically to meet up with basic needs of the family. Therefore, the government and development organizations should enhance the effectiveness of cooperative societies through sustained awareness campaign and financial support for sustainable development.